Efficacy of laparoscopic inguinal hernia in day surgery mode and inpatient surgery mode in China: A meta-analysis. Issue 8 (22nd February 2023) - Zhong, Yang; He, Miao; Liu, Zhi; Chen, Jian Yu; Lv, Xiao Jiang; Liu, Mao; Wen, Ai Ping; Qin, Long; Li, Jian Shui
Abstract : Background: In China, laparoscopic inguinal hernia repair (LIHR) under the day surgery mode (DSM) has developed rapidly as an important surgical method for inguinal hernia repair, and it has unique advantages in many aspects. Compared with inpatient surgery mode (ISM), there are some differences in intraoperative and postoperative related indicators, hospitalization costs, and patient satisfaction. Many studies have shown that LIHR in DSM can significantly shorten hospital stay, effectively reduce hospitalization costs, and improve patient satisfaction. Accordingly, this study aimed to compare the differences in intraoperative and postoperative related indicators, hospitalization costs, and patient satisfaction of LIHR between DSM and ISM in China. Methods: The PubMed/Medline, EMBASE, Cochrane Library, China National Knowledge Infrastructure, and Wan Fang databases were searched for randomized controlled trials, cohort studies from the establishment of the database to July 1, 2022. Odds ratio (OR), mean difference, standardized mean difference (SMD), and 95% confidence interval were selected as the effect scale indices for the evaluation of the difference in hospitalization costs, hospital stay, operation time, recovery time, complications, and patient satisfaction. All of these were compared using RevMan 5.3 Software (The Cochrane Collaboration, Copenhagen, Denmark). Results: Nine studies involving 1176 patients, 590 in the DSM group and 586 in the ISM group, were included. The hospital stay (d) (SMD = −7.27, 95% confidence interval, CI: −8.68 to −5.87, P < .001), hospitalization costs (SMD = −7.89, 95% CI: −10.25 to −5.53, P < .001) in DSM group were significantly lower than the ISM group. Additionally, the patient dissatisfaction (OR = 0.05, 95% CI: 0.01–0.17, P < .001) in DSM group was significantly lower than the ISM group. Nevertheless, no significant differences were found in the operation time (minute) (mean difference = −0.32, 95% CI: −1.78 to 1.14, P = .67), recovery time (h) (SMD = −3.27, 95% CI: −6.95 to 0.41, P = .08), and postoperative complications (OR = 0.80, 95% CI: 0.47–1.36, P = .41) between the 2 groups. Conclusion: In China, compared with ISM, LIHR under DSM can significantly shorten hospital stay, greatly reduce hospitalization costs, and significantly improve patient satisfaction. There were no significant differences in operation time, recovery time and postoperative complications.